Pengenalan Sistem Pertanian Organik Melalui Penyuluhan Pada Gabungan Kelompok Tani (Gapoktan) di Desa Tempos Kecamatan Gerung Lombok Barat - Baiq Azizah Haryantini; Made Sunantra (Jurnal Gema Ngabdi, 2020)
Aim of Community service activities, namely counse to explain and invite farmers in Tempos Village Gerung District, West Lombok Regency, to be familiar with the implementation of the organic farming system, and encourage farming communities to utilize the potential of natural resources well and wisely to protect agricultural land from degradation (damage) and good production in the long term. For this reason, counseling has been carried out in the agricultural sector, namely the organic farming system with the results of farmers and the community understands that the organic farming system has the potential to be implemented on agricultural land in the village of Tempos, and to improve soil health and protect the environment from degradation (damage) in the long term (sustainable). Farmers are motivated to improve their ability to manage their farming with an organic farming system.